1968
DOI: 10.1111/j.1476-5381.1968.tb00451.x
|View full text |Cite
|
Sign up to set email alerts
|

VASCULAR LESIONS IN RABBITS INFECTED WITH TRYPANOSOMA (TRYPANOZOON) BRUCEI

Abstract: When a rabbit is inoculated with Trypanosoma (Trypanozoon) brucei usually only a few parasites appear in the circulating blood. Nevertheless, 3 to 5 weeks after inoculation the animal becomes listless, the fur staring, and the ears pale, thick and heavy. The tissues around the eyes are swollen, and scabby necrotic lesions appear in the skin of the face, ears and scrotum. The animal dies several weeks after inoculation and the cause of death is unknown.This paper describes some observations on the circulation i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
11
0

Year Published

1968
1968
1999
1999

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(11 citation statements)
references
References 13 publications
0
11
0
Order By: Relevance
“…The accumulation of trypanosomes and the cellular inflammatory exudate in tissues were often accompanied by focal, and occasionally diffuse, areas of acute necrosis of the interstitial and parenchymatous tissues. This infiltration of mononuclear cells into infected tissues and the necrosis may indicate, as suggested by GOODWIN and HOOK [6], that a cell-mediated immunological response of the delayed hypersensitivity type is tlie cause of tlie injurious effects.…”
Section: Disciissionmentioning
confidence: 78%
“…The accumulation of trypanosomes and the cellular inflammatory exudate in tissues were often accompanied by focal, and occasionally diffuse, areas of acute necrosis of the interstitial and parenchymatous tissues. This infiltration of mononuclear cells into infected tissues and the necrosis may indicate, as suggested by GOODWIN and HOOK [6], that a cell-mediated immunological response of the delayed hypersensitivity type is tlie cause of tlie injurious effects.…”
Section: Disciissionmentioning
confidence: 78%
“…A positive correlation was found between the kinins and the number of trypanosomes in the blood [23]. In the rabbit the ears were reported to be oedematous, and microscopically there was a chronic angiitis and cellular and exudative inflammatory reaction [24,119,1201. Accompanying the reaction in the ears there was a decrease in red blood cells, packed cell volume, and haemoglobin.…”
mentioning
confidence: 99%
“…First, in experimental rabbit trypanosomiasis, each wave of parasitemia is caused by trypanosomes with antigens different from those of the predecessors, against which antibody has already been produced (16). Second, Goodwin and Hook (17) have shown that the major pathologic changes in rabbits infected with Trypanosonta brucei are vascular lesions, thrombus formation, and increased vascular permeability. Finally, kinin concentrations are increased in experimental infections of laboratory animals (18) and volunteers (19).…”
Section: Discussionmentioning
confidence: 99%